ICSI outcome after microdissection testicular sperm extraction, testicular sperm aspiration and ejaculated sperm - Klami, Rauni (Elsevier, 2025)
We conducted a case-controlled single-center cohort study to evaluate the intracytoplasmic sperm injection (ICSI) outcome in severe male infertility with different methods of sperm obtention. The data was compiled from a tertiary university hospital. The micro-TESE procedures were performed from 2008 to 2023, with a sperm recovery rate (SRR) of 45 %. The ICSI treatments were carried out between 2011 and 2023. The aim of the study was to compare the ICSI outcome using sperm obtained by microdissection testicular extraction (micro-TESE), testicular sperm aspiration (TESA), and ejaculated sperm with sperm concentration less than 15 million per milliliter. We included a total of 462 ICSI cycles, of which 340 ICSIs with ejaculated sperm of men with oligozoospermia, with or without asthenozoospermia or teratozoospermia (OAT group), 51 ICSIs with TESA sperm of men with obstructive azoospermia (OA, TESA group), and 71 ICSIs with micro-TESE sperm of men with non-obstructive azoospermia (NOA, micro-TESE group). The patient characteristics, fertilization rate, pregnancy rate, and pregnancy outcome data were similar between the groups. The fertilization rates were 66.0 % in the OAT group, 68.3 % in the TESA group and 62.8 % in the micro-TESE group and live birth rate per embryo transfer were 23.7 %, 28.9 %, and 25.0 %, respectively, without statistical difference. The obstetrical outcome was similar in all the groups. The overall clinical results in all ICSI cycles performed for treating severe male factor infertility were similar, independent of the method of collection of spermatozoa. The results also confirm the efficacy of micro-TESE in the treatment of severe male factor infertility.